Characterizing mechanisms of caregiver-mediated naturalistic developmental behavioral interventions for autistic toddlers: A randomized clinical trial - Jones, Maranda K; Sone, Bailey J; Grauzer, Jeffrey; Sudec, Laura; Kaat, Aaron; Roberts, Megan Y (Autism : the international journal of research and practice, 2024)
To address the variability of naturalistic developmental behavioral intervention outcomes, the current study sought to isolate the effects of the instructional strategies of caregiver-mediated naturalistic developmental behavioral interventions. In this comparative efficacy trial, mothers of 111 autistic children (18–48 months) were randomized to learn one of two sets of naturalistic developmental behavioral intervention language facilitation strategies (responsive or directive). We aimed to characterize the effect of strategy type on language outcomes and explore the extent to which joint engagement outcomes mediated language outcomes. Children in the directive condition had significantly greater scores across multiple language assessments. At follow-up, the effect of strategy type on the frequency of spontaneous directed communication acts was fully mediated by coordinated joint engagement (indirect effect = −2.070, 95% CI = [−4.394, −0.06], p < 0.05). Thus, children may benefit from caregiver prompts to facilitate long-term language outcomes. The current study is an initial step in the identification of the mechanisms of caregiver-mediated NDBIs. Lay abstract Caregiver-mediated early interventions support caregivers’ use of strategies to improve their young autistic child’s communication. In the current clinical trial, we sought to isolate the most effective strategies to improve short-term and long-term child communication outcomes. Results demonstrated how children may benefit from caregiver prompts to facilitate long-term language outcomes. In conclusion, the current study improves our understanding of how early intervention facilitates child communication outcomes.